Cryo-EM structures of inhibitory antibodies complexed with arginase 1 provide insight into mechanism of action - Rachel L. Palte (Nature Portfolio, 2021)
Palte et al provide cryo-EM structures of five potent and inhibitory monoclonal antibodies bound to human Arginase 1, a T-cell modulating metalloenzyme and a cancer drug target. They provide structural insights that will aid in the evaluation of these antibodies as therapeutic inhibitors of arginasemediated T-cell suppression.